A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

GOOS Essential Ocean Variables: the backbone of a sustained and evolving global ocean observing system - Belén Martín Míguez; Emma Heslop; Narissa Bax; Lisandro Benedetti-Cecchi; Gabrielle Canonico; Kim Currie; Karen Evans; Albert S. Fischer; Véronique Garçon; Maria Hood; Johannes Karstensen; Ana Lara-López; et al. (Frontiers in Marine Science, 2026)
The need for ocean information has never been greater. From climate change to food security and extreme events, we need to understand the role of the ocean and better predict change and impact. This is only possible with the sustained collection of a key set of ocean observations. The Global Ocean Observing System (GOOS) coordinates international efforts to collect these Essential Ocean Variables (EOVs), which span physics, biogeochemistry, biology and ecosystem realms. Guided by three expert panels, these EOVs are used to define the needs and design of a sustained, fit for purpose global ocean observing system, aimed at maximizing investments in observing infrastructure. As the GOOS EOVs are increasingly used, it has become important to discuss and refine the understanding of this framework, to ensure that the right balance is struck between their essential nature and the need to expand to new domains and integrate with key global policies. In this paper we provide a description of the EOV framework, discuss some of the challenges in implementing it, and identify a set of recommendations for GOOS and the ocean observing community to take forward. These recommendations include increasing the transparency of the EOV adoption process, and the need to periodically assess the EOVs in consultation with observing communities and with the entities managing other global essential variable frameworks in cross cutting realms such as climate and biodiversity. This will contribute to building a useful and responsive global ocean observing system that delivers the observations required to meet societal needs.

Global ocean indicators: Marking pathways at the science-policy nexus - Karina von Schuckmann; Alex Godoy-Faundez; Véronique Garçon; Frank E. Muller-Karger; Karen Evans; Ward Appeltans; Narissa Bax; Lisandro Benedetti Cecchi; Anthony Bernard; Kim Bernard; Jarret Byrnes; Gabrielle Canonico; et al. (Marine Policy, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Crustacean assemblage structure over the Charlie-Gibbs Fracture Zone of the Mid-Atlantic Ridge collected during the 2009 Henry B. Bigelow expedition - Kathryn E. Medina; Rosanna J. Milligan; Tracey T. Sutton; Tamara Frank (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Climate Extremes in the New Zealand Region: Mechanisms, Impacts and Attribution - M. James Salinger; Kevin E. Trenberth; Howard J. Diamond; Erik Behrens; B. Blair Fitzharris; Nicholas Herold; Robert O. Smith; Phil J. Sutton; Michael C. T. Trought (International Journal of Climatology, 2024)
As global surface temperatures have increased with human‐induced climate change, notable compound climate extremes in the New Zealand (NZ) region associated with atmospheric heatwaves (AHWs) and marine heatwaves (MHWs) have occurred in the past 6 years. Natural modes of variability that also played a key role regionally include the Interdecadal Pacific Oscillation (IPO), El Niño/Southern Oscillation (ENSO) and changes in the location and strength of the westerlies as seen in the Southern Annular Mode (SAM). Along with mean warming of 0.8°C since 1900, a negative phase of the IPO, La Niña phase of ENSO and a strongly positive SAM contributed to five compound warm extremes in the extended austral summer seasons (NDJFM) of 1934/35, 2017/18, 2018/19, 2021/22 and 2022/23. These are the most intense coupled ocean/atmosphere (MHWs/AHWs) heatwaves on record with average temperature anomalies over land and sea +0.8°C to 1.1°C above 1991–2020 averages. The number of days above 25°C and above the 90th percentile of maximum temperature has increased, while the number of nights below 0°C and below the 10th percentile has decreased. Coastal waters around NZ recently experienced their longest MHW in the satellite era (1982‐present) of 289 days through 2023. The estimated recurrence interval reduces from 1 in 300‐years for the AHW event during the 1930s climate to a 1 in 25‐year event for the most recent decade. Consequences include major loss of ice of almost one‐third volume from Southern Alps glaciers from 2017 to 2021 with rapid melt of seasonal snow in all four cases. Above‐average temperatures in the December/January grape flowering period resulted in advances in veraison (the onset of ripening); and higher‐than‐average grape yields in 2022 and 2023 vintages. Marine impacts include widespread sea‐sponge bleaching around northern and southern NZ.

Modelling pollutants transport scenarios based on the X-Press Pearl disaster - Julia Rulent; Molly K. James; Ponnambalam Rameshwaran; Jennifer E. Jardine; Anna Katavouta; Sarah Wakelin; Ruchira Jayathilaka; Kanapathipillai Arulananthan; Jason Holt; Mark A. Sutton; Yuri Artioli (Marine Pollution Bulletin, 2024)

Global screening of base excision repair in nucleosome core particles - Treshaun B. Sutton; Danielle L. Sawyer; Tasmin Naila; Joann B. Sweasy; Alan E. Tomkinson; Sarah Delaney (DNA Repair, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Nutritional Awareness Among Patients in the Reproductive Endocrinology Setting - N. Shipley; N. Chappell; E. Sutton; E. Hall (Journal of the Academy of Nutrition and Dietetics, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Spatially limited pathogen pollution in an invasive tick and host system - Carrie E. De Jesus; Madison E. A. Harman; Amber Sutton; Stephen Bredin; Christina M. Romagosa; Samantha M. Wisely (Biological Invasions, 2024)
Expansion of global commerce has facilitated pathogen pollution via the transportation and translocation of invasive species and their associated parasites and pathogens. In Florida, imported cane toads ( Rhinella horribilis ) were accidentally and intentionally released on multiple occasions. Early populations were found to be infested with the invasive tick, Amblyomma rotundatum , yet it is unknown if these ticks dispersed with their hosts as cane toads spread throughout much of the state. The objectives of our investigation were to (1) determine if there are fewer tick infestations on toads at the periphery than at the core of their distribution as predicted by founder effect events, and (2) identify if ticks were infected with exotic pathogens. We captured toads from 10 populations across Florida. We collected ticks, vent tissue, and tick attachment site tissue from each toad, then tested samples for bacteria in the genus, Rickettsia . We found that 3/10 populations had toads that were infested with A. rotundatum , and infested individuals were in the earliest introduced populations at the core of their distribution. Pathogen testing confirmed Rickettisa bellii in ticks, but not in toad tissues. Haplotype networks could not clearly distinguish if R. bellii in Florida was more closely related to North or South American strains, but host-tick associations suggest that the pathogen was exotic to Florida. Our investigation demonstrated that an invasive species facilitated the introduction of parasites and pathogens into Florida, yet the invasive tick species encountered limitations to dispersal on this host species.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Blue carbon pathways for climate mitigation: Known, emerging and unlikely - Jennifer Howard; Ariana E. Sutton-Grier; Lindsey S. Smart; Christian C. Lopes; Jill Hamilton; Joan Kleypas; Stefanie Simpson; Jennifer McGowan; Albert Pessarrodona; Heidi K. Alleway; Emily Landis (Marine Policy, 2023)

Numerical modeling of wave attenuation: implications of representing vegetation found in coastal saltmarshes in the Chesapeake Bay - Tyler Miesse; Andre de Souza de Lima; Arslaan Khalid; Felicio Cassalho; Daniel J. Coleman; Celso M. Ferreira; Ariana E. Sutton-Grier (Environmental Monitoring and Assessment, 2023)

Insights from the management of offshore energy resources: Toward an ecosystem-services based management approach for deep-ocean industries - M. Emilia Bravo; Miriam I. Brandt; Jesse M. A. van der Grient; Thomas G. Dahlgren; Patricia Esquete; Sabine Gollner; Daniel O. B. Jones; Lisa A. Levin; Craig R. McClain; Bhavani E. Narayanaswamy; Tracey Sutton; Lissette Victorero; et al. (Frontiers in Marine Science, 2023)
The deep ocean comprises complex ecosystems made up of numerous community and habitat types that provide multiple services that benefit humans. As the industrialization of the deep sea proceeds, a standardized and robust set of methods and metrics need to be developed to monitor the baseline conditions and any anthropogenic and climate change-related impacts on biodiversity, ecosystem function, and ecosystem services. Here, we review what we have learned from studies involving offshore-energy industries, including state-of-the-art technologies and strategies for obtaining reliable metrics of deep-sea biodiversity and ecosystem function. An approach that includes the detection and monitoring of ecosystem services, with open access to baseline data from multiple sectors, can help to improve our global capacity for the management of the deep ocean.

The diagnostic utility of hypophosphatemia for differentiating generalized tonic-clonic seizures from syncope in dogs: A case control study - E. Kelmer; D.G. Ohad; M.H. Shamir; O. Chai; S. Lavie; G.A. Sutton; I. Aroch; S. Klainbart (The Veterinary Journal, 2023)

Improving suitability of urban canals and canalized rivers for transportation, thermal energy extraction and recreation in two European delta cities - E. Suzanne van der Meulen; Frans H. M. van de Ven; Pieter R. van Oel; Huub H. M. Rijnaarts; Nora B. Sutton (Ambio, 2023)
Canals and canalized rivers form a major part of surface water systems in European delta cities and societal ambitions to use these waters increase. This is the first assessment of how suitability of these waters can improve for three important uses: transportation, thermal energy extraction (TEE) and recreation. We assess suitability with Suitability Indices (SIs) and identify which alterations in the water system are needed to improve SI scores in Amsterdam, The Netherlands, and Ghent, Belgium. The results show spatial variability in suitability scores. Current suitability for transportation is low (SI score = 1) to excellent (SI score = 4), for TEE fair (SI score = 2) to excellent (SI score = 4), and suitability for recreation is low (SI score = 1). Suitability could improve by enlarging specific waterway dimensions, increasing discharge and clarity, and by enhancing microbiological water quality. The same methodology can be applied to optimize designs for new water bodies and for more water uses.

Profiling of Fusarium head blight resistance QTL haplotypes through molecular markers, genotyping-by-sequencing, and machine learning - Zachary J. Winn; Jeanette Lyerly; Brian Ward; Gina Brown-Guedira; Richard E. Boyles; Mohamed Mergoum; Jerry Johnson; Stephen Harrison; Ali Babar; Richard E. Mason; Russell Sutton; J. Paul Murphy (Theoretical and Applied Genetics, 2022)

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The genetics of vigour-related traits in chickpea (Cicer arietinum L.): insights from genomic data - Duong T. Nguyen; Julie E. Hayes; Judith Atieno; Yongle Li; Ute Baumann; Angela Pattison; Helen Bramley; Kristy Hobson; Manish Roorkiwal; Rajeev K. Varshney; Timothy D. Colmer; Tim Sutton (Theoretical and Applied Genetics, 2022)

What the pluck? The theft of mammal hair by birds is an overlooked but common behavior with fitness implications - Henry S. Pollock; Sean E. MacDonald; Jeferson Vizentin‐Bugoni; Jeffrey D. Brawn; Zachary S. Sutton; Mark E. Hauber (Ecology, 2021)

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Moving from trends to benchmarks by using regression tree analysis to find inbreeding thresholds in a critically endangered bird - Alison M. Flanagan; Bryce Masuda; Catherine E. Grueber; Jolene T. Sutton (Conservation Biology, 2021)
Understanding how inbreeding affects endangered species in conservation breeding programs is essential for their recovery. The Hawaiian Crow (‘Alalā) ( Corvus hawaiiensis ) is one of the world's most endangered birds. It went extinct in the wild in 2002, and, until recent release efforts starting in 2016, nearly all of the population remained under human care for conservation breeding. Using pedigree inbreeding coefficients ( F ), we evaluated the effects of inbreeding on Hawaiian Crow offspring survival and reproductive success. We used regression tree analysis to identify the level of inbreeding (i.e., inbreeding threshold) that explains a substantial decrease in ‘Alalā offspring survival to recruitment. Similar to a previous study of inbreeding in ‘Alalā, we found that inbreeding had a negative impact on offspring survival but that parental (vs. artificial) egg incubation improved offspring survival to recruitment. Furthermore, we found that inbreeding did not substantially affect offspring reproductive success, based on the assumption that offspring that survive to adulthood breed with distantly related mates. Our novel application of regression tree analysis showed that offspring with inbreeding levels exceeding F = 0.098 were 69% less likely to survive to recruitment than more outbred offspring, providing a specific threshold value for ongoing population management. Our results emphasize the importance of assessing inbreeding depression across all life history stages, confirm the importance of prioritizing parental over artificial egg incubation in avian conservation breeding programs, and demonstrate the utility of regression tree analysis as a tool for identifying inbreeding thresholds, if present, in any pedigree‐managed population.

Coastal Wetlands Exposure to Storm Surge and Waves in the Albemarle-Pamlico Estuarine System during Extreme Events - Felício Cassalho; Tyler W. Miesse; André de S. de Lima; Arslaan Khalid; Celso M. Ferreira; Ariana E. Sutton-Grier (Wetlands, 2021)

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

Climate‐driven carry‐over effects negatively influence population growth rate in a food‐caching boreal passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Global Change Biology, 2021)
Understanding how events throughout the annual cycle are linked is important for predicting variation in individual fitness, but whether and how carry‐over effects scale up to influence population dynamics is poorly understood. Using 38 years of demographic data from Algonquin Provincial Park, Ontario, and a full annual cycle integrated population model, we examined the influence of environmental conditions and density on the population growth rate of Canada jays ( Perisoreus canadensis ), a resident boreal passerine that relies on perishable cached food for over‐winter survival and late‐winter breeding. Our results demonstrate that fall environmental variables, most notably the number of freeze–thaw events, carried over to influence late‐winter fecundity, which, in turn, was the main vital rate driving population growth. These results are consistent with the hypothesis that warmer and more variable fall conditions accelerate the degradation of perishable stored food that is relied upon for successful reproduction. Future warming during the fall and winter may compromise the viability of cached food that requires consistent subzero temperatures for effective preservation, potentially exacerbating climate‐driven carry‐over effects that impact long‐term population dynamics.

Environmental conditions modulate compensatory effects of site dependence in a food‐caching passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Ecology, 2021)
Although density regulates the abundance of most wild animal populations by influencing vital rates, such as fecundity and survival, the mechanisms responsible for generating negative density dependence are unclear for many species. Site dependence occurs when there is preferential filling of high‐quality territories, which results in higher per capita vital rates at low densities because a larger proportion of occupied territories are of high quality. Using 41 yr of territory occupancy and demographic data, we investigated whether site dependence was a mechanism acting to influence fecundity and, by extension, regulate a population of Canada Jays in Algonquin Provincial Park, Ontario, Canada. As predicted by site dependence, the proportion of occupied territories that were of high quality was negatively correlated with population density and periods of vacancy were shorter for high‐quality territories than for low‐quality territories. We also found evidence that per capita fecundity was positively related to the proportion of occupied territories that were of high quality, but only when environmental conditions, which influence the entire population, were otherwise poor for breeding. Our results suggest that site dependence likely plays a role in regulating this population but that environmental conditions can modulate the strength of density dependence.

Trends in Demand of Urban Surface Water Extractions and in Situ Use Functions - E. S. van der Meulen; N. B. Sutton; F. H. M. van de Ven; P. R. van Oel; H. H. M. Rijnaarts (Water Resources Management, 2020)
Scientific literature currently lacks comprehensive understanding of urban surface water use functions. This hampers sound analysis of the demand and potential supply of these functions. This study provides a comprehensive overview of potential use functions, by integrating knowledge from ecosystem services and integrated urban water management fields. Analysis of water-related management plans for Toronto and Amsterdam shows that surface water is currently being used for a variety of functions related to nutrition, energy, water regulation, recreation, symbolic use, transportation and floating buildings. Notably, many use functions involve in situ use, rather than water extractions. Interviewed water managers and spatial planners in both cities expect demand of most use functions to increase by 2040, especially demand for thermal energy extraction, recreation and transportation. Some identified novel demands, such as climate regulation and reuse of waste products from waterway maintenance. Increasing demand is mainly driven by urban growth, climate change and sustainability ambitions. This study found urban surface water uses that are usually not acknowledged in scientific literature on urban water management. This comprehensive overview supports planning, design, and maintenance of urban surface waters, laying the foundation for future research on supply and demand of urban water use functions.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Raising young with limited resources: supplementation improves body condition and advances fledging of Canada Jays - Nikole E. Freeman; D. Ryan Norris; Alex O. Sutton; Amy E. M. Newman (Ecology, 2020)
Food availability early in life can play a vital role in an individual's development and success, but experimental evidence for the direct effects of food on body condition, physiology, and survival of young animals in the wild is still relatively scarce. Food‐caching Canada Jays ( Perisoreus canadensis ) begin breeding in the late winter and, therefore, rely on either cached food or seemingly limited quantities of fresh food to feed nestlings in the early spring. Using a 2‐yr food supplementation experiment conducted during the nestling period and 40 yr of observational data on food supplemented by the public, we examined whether food quantity during early life influenced the physiology, body condition, timing of fledging, and survival of young Canada Jays in Algonquin Provincial Park, Ontario, Canada . Experimental food supplementation of breeding pairs advanced the fledging date of young by 24% (5.5 d) compared to controls. In 1 yr of the experiment, nestlings raised on experimentally supplemented territories had lower feather corticosterone concentrations and were in higher body condition than controls. Across treatment and control nests, young that successfully fledged had lower concentrations of feather corticosterone and were in higher body condition than those that did not fledge. Based on 40 yr of observational data, nestling body condition was positively related to the degree of food supplementation by park visitors and nestlings in higher body condition were more likely to be observed in the population in the following fall. Our results demonstrate how food availability early in life can have important downstream consequences on metrics related to individual fitness, including first year survival.

Conservation of Wetlands and Other Coastal Ecosystems: a Commentary on their Value to Protect Biodiversity, Reduce Disaster Impacts, and Promote Human Health and Well-Being - Ariana E. Sutton-Grier; Paul A. Sandifer (Wetlands, 2019)

Monofunctional platinum(II) compounds and nucleolar stress: is phenanthriplatin unique? - Christine E. McDevitt; Matthew V. Yglesias; Austin M. Mroz; Emily C. Sutton; Min Chieh Yang; Christopher H. Hendon; Victoria J. DeRose (JBIC Journal of Biological Inorganic Chemistry, 2019)

Covariations between plant functional traits emerge from constraining parameterization of a terrestrial biosphere model - Marc Peaucelle; Cédric Bacour; Philippe Ciais; Nicolas Vuichard; Sylvain Kuppel; Josep Peñuelas; Luca Belelli Marchesini; Peter D. Blanken; Nina Buchmann; Jiquan Chen; Nicolas Delpierre; Ankur R. Desai; et al. (Global Ecology and Biogeography, 2019)
Aim The mechanisms of plant trait adaptation and acclimation are still poorly understood and, consequently, lack a consistent representation in terrestrial biosphere models (TBMs). Despite the increasing availability of geo‐referenced trait observations, current databases are still insufficient to cover all vegetation types and environmental conditions. In parallel, the growing number of continuous eddy‐covariance observations of energy and CO 2 fluxes has enabled modellers to optimize TBMs with these data. Past attempts to optimize TBM parameters mostly focused on model performance, overlooking the ecological properties of ecosystems. The aim of this study was to assess the ecological consistency of optimized trait‐related parameters while improving the model performances for gross primary productivity (GPP) at sites. Location Worldwide. Time period 1992–2012. Major taxa studied Trees and C 3 grasses. Methods We optimized parameters of the ORCHIDEE model against 371 site‐years of GPP estimates from the FLUXNET network, and we looked at global covariation among parameters and with climate. Results The optimized parameter values were shown to be consistent with leaf‐scale traits, in particular, with well‐known trade‐offs observed at the leaf level, echoing the leaf economic spectrum theory. Results showed a marked sensitivity of trait‐related parameters to local bioclimatic variables and reproduced the observed relationships between traits and climate. Main conclusions Our approach validates some biological processes implemented in the model and enables us to study ecological properties of vegetation at the canopy level, in addition to some traits that are difficult to observe experimentally. This study stresses the need for: (a) implementing explicit trade‐offs and acclimation processes in TBMs; (b) improving the representation of processes to avoid model‐specific parameterization; and (c) performing systematic measurements of traits at FLUXNET sites in order to gather information on plant ecophysiology and plant diversity, together with micro‐meteorological conditions.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Variation in rod spectral sensitivity of fishes is best predicted by habitat and depth - Lorian E. Schweikert; Eleanor M. Caves; Sarah E. Solie; Tracey T. Sutton; Sönke Johnsen (Journal of Fish Biology, 2019)
Rod spectral sensitivity data ( λ max ), measured by microspectrophotometry, were compiled for 403 species of ray‐finned fishes in order to examine four hypothesized predictors of rod spectral sensitivity (depth, habitat, diet and temperature). From this database, a subset of species that were known to be adults and available on a published phylogeny ( n = 210) were included in analysis, indicating rod λ max values averaging 503 nm and ranging from 477 to 541 nm. Linear models that corrected for phylogenetic relatedness showed that variation in rod sensitivity was best predicted by habitat and depth, with shorter wavelength λ max values occurring in fishes found offshore or in the deep sea. Neither diet, nor the interaction of diet and habitat, had significant explanatory power. Although temperature significantly correlated with rod sensitivity, in that fishes in temperate latitudes had longer wavelength rod λ max values than those in tropical latitudes, sampling inequity and other confounds require the role of the temperature to be studied further. Together, these findings indicate that fish rod λ max is influenced by several ecological factors, suggesting that selection can act on even small differences in fish spectral sensitivity.

Statin therapy and herpes virus reactivation—response to Zuin et al. paper - Jonathan E. Sutton; Negar Maghsoodi; Alexa R. Shipman; Kate E. Shipman (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Training population selection and use of fixed effects to optimize genomic predictions in a historical USA winter wheat panel - J. Martin Sarinelli; J. Paul Murphy; Priyanka Tyagi; James B. Holland; Jerry W. Johnson; Mohamed Mergoum; Richard E. Mason; Ali Babar; Stephen Harrison; Russell Sutton; Carl A. Griffey; Gina Brown-Guedira (Theoretical and Applied Genetics, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Restructuring of a mutualism following introduction of Australian fig trees and pollinating wasps to Europe and the USA - E. J. Morgan; T. L. Sutton; C. T. Darwell; J. M. Cook (Biological Invasions, 2018)

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Reciprocal translocation of small numbers of inbred individuals rescues immunogenetic diversity - Catherine E. Grueber; Jolene T. Sutton; Sol Heber; James V. Briskie; Ian G. Jamieson; Bruce C. Robertson (Molecular Ecology, 2017)
Genetic rescue can reduce inbreeding depression and increase fitness of small populations, even when the donor populations are highly inbred. In a recent experiment involving two inbred island populations of the New Zealand South Island robin, Petroica australis, reciprocal translocations improved microsatellite diversity and individual fitness. While microsatellite loci may reflect patterns of genome‐wide diversity, they generally do not indicate the specific genetic regions responsible for increased fitness. We tested the effectiveness of this reciprocal translocation for rescuing diversity of two immunogenetic regions: Toll‐like receptor ( TLR ) and major histocompatibility complex ( MHC ) genes. We found that the relatively small number of migrants (seven and ten per island) effectively brought the characteristic TLR gene diversity of each source population into the recipient population. However, when migrants transmitted TLR alleles that were already present at high frequency in the recipient population, it was possible for offspring of mixed heritage to have decreased gene diversity compared to recipient population diversity prior to translocation. In contrast to TLR s, we did not observe substantial changes in MHC allelic diversity following translocation, with limited evidence of a decrease in differentiation, perhaps because most MHC alleles were observed at both sites prior to the translocation. Overall, we conclude that small numbers of migrants may successfully restore the diversity of immunogenetic loci with few alleles, but that translocating larger numbers of animals would provide additional opportunity for the genetic rescue of highly polymorphic immunity regions, such as the MHC , even when the source population is inbred.

The provision of dietary and physical activity advice for men diagnosed with prostate cancer: a qualitative study of the experiences and views of health care professionals, patients and partners - Eileen Sutton; Lucy E. Hackshaw-McGeagh; Jonathan Aning; Amit Bahl; Anthony Koupparis; Raj Persad; Richard M. Martin; J. Athene Lane (Cancer Causes & Control, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Influence of the Leeuwin Current on the epipelagic euphausiid assemblages of the south-east Indian Ocean - Alicia L. Sutton; Lynnath E. Beckley (Hydrobiologia, 2016)

Nicotine-induced cortical activation among nonsmokers with moderation by trait cognitive control - Steven K. Sutton; Kate Janse Van Rensburg; Kade G. Jentink; David J. Drobes; David E. Evans (Psychopharmacology, 2016)

Recommendations for the future of recreational fisheries to prepare the social‐ecological system to cope with change - R. Arlinghaus; S. J. Cooke; S. G. Sutton; A. J. Danylchuk; W. Potts; K. de M. F. Freire; J. Alós; E. T. da Silva; I. G. Cowx; R. van Anrooy (Fisheries Management and Ecology, 2016)
This paper presents conclusions and recommendations that emerged from the 7th World Recreational Fishing Conference ( WRFC ) held in Campinas, Brazil in September 2014. Based on the recognition of the immense social and economic importance of recreational fisheries coupled with weaknesses in robust information about these fisheries in many areas of the world, particularly in many economies in transition, it is recommended to increase effort to build effective governance arrangements and improve monitoring and assessment frameworks in data‐poor situations. Moreover, there is a need to increase interdisciplinary studies that will foster a systematic understanding of recreational fisheries as complex adaptive social‐ecological systems. To promote sustainable recreational fisheries on a global scale, it is recommended the detailed suggestions for governance and management outlined in the United Nations Food and Agricultural Organization Technical Guidelines for Responsible Fisheries: Recreational Fisheries are followed.

Leveraging Carbon Services of Coastal Ecosystems for Habitat Protection and Restoration - Ariana E. Sutton-Grier; Amber Moore (Coastal Management, 2016)

High-resolution skim genotyping by sequencing reveals the distribution of crossovers and gene conversions in Cicer arietinum and Brassica napus - Philipp E. Bayer; Pradeep Ruperao; Annaliese S. Mason; Jiri Stiller; Chon-Kit Kenneth Chan; Satomi Hayashi; Yan Long; Jinling Meng; Tim Sutton; Paul Visendi; Rajeev K. Varshney; Jacqueline Batley; et al. (Theoretical and Applied Genetics, 2015)

Cortical activity differs during nicotine deprivation versus satiation in heavy smokers - David E. Evans; Steven K. Sutton; Jason A. Oliver; David J. Drobes (Psychopharmacology, 2015)

Quantifying alosine prey in the diets of marine piscivores in the Gulf of Maine - S. P. McDermott; N. C. Bransome; S. E. Sutton; B. E. Smith; J. S. Link; T. J. Miller (Journal of Fish Biology, 2015)
The objectives of this work were to quantify the spatial and temporal distribution of the occurrence of anadromous fishes (alewife Alosa pseudoharengus , blueback herring Alosa aestivalis and American shad Alosa sapidissima ) in the stomachs of demersal fishes in coastal waters of the north‐west Atlantic Ocean. Results show that anadromous fishes were detectable and quantifiable in the diets of common marine piscivores for every season sampled. Even though anadromous fishes were not the most abundant prey, they accounted for c. 5–10% of the diet by mass for several marine piscivores. Statistical comparisons of these data with fish diet data from a broad‐scale survey of the north‐west Atlantic Ocean indicate that the frequency of this trophic interaction was significantly higher within spatially and temporally focused sampling areas of this study than in the broad‐scale survey. Odds ratios of anadromous predation were as much as 460 times higher in the targeted sampling as compared with the broad‐scale sampling. Analyses indicate that anadromous prey consumption was more concentrated in the near‐coastal waters compared with consumption of a similar, but more widely distributed species, the Atlantic herring Clupea harengus . In the context of ecosystem‐based fisheries management, the results suggest that even low‐frequency feeding events may be locally important, and should be incorporated into ecosystem models.

Insights on surface-water/groundwater exchange in the upper Floridan aquifer, north-central Florida (USA), from streamflow data and numerical modeling - James E. Sutton; Elizabeth J. Screaton; Jonathan B. Martin (Hydrogeology Journal, 2015)

Simulation of CO2 and Attribution Analysis at Six European Peatland Sites Using the ECOSSE Model - M. Abdalla; A. Hastings; M. J. Bell; J. U. Smith; M. Richards; M. B. Nilsson; M. Peichl; M. O. Löfvenius; M. Lund; C. Helfter; E. Nemitz; M. A. Sutton; et al. (Water, Air, & Soil Pollution, 2014)

Considering “Coastal Carbon” in Existing U.S. Federal Statutes and Policies - Linwood H. Pendleton; Ariana E. Sutton-Grier; David R. Gordon; Brian C. Murray; Britta E. Victor; Roger B. Griffis; Jen A.V. Lechuga; Chandra Giri (Coastal Management, 2013)

The Bottleneck Effect in Lung Cancer Clinical Trials - Luis E. Gonzalez; Steven K. Sutton; Christie Pratt; Matthew Gilbertson; Scott Antonia; Gwendolyn P. Quinn (Journal of Cancer Education, 2013)

Characterization of MHC class II B polymorphism in bottlenecked New Zealand saddlebacks reveals low levels of genetic diversity - Jolene T. Sutton; Bruce C. Robertson; Catherine E. Grueber; Jo-Ann L. Stanton; Ian G. Jamieson (Immunogenetics, 2013)

Anaerobic Metabolism in Tidal Freshwater Wetlands: III. Temperature Regulation of Iron Cycling - Allyson L. Bullock; Ariana E. Sutton-Grier; J. Patrick Megonigal (Estuaries and Coasts, 2013)

Anaerobic Metabolism in Tidal Freshwater Wetlands: I. Plant Removal Effects on Iron Reduction and Methanogenesis - Jason K. Keller; Ariana E. Sutton-Grier; Allyson L. Bullock; J. Patrick Megonigal (Estuaries and Coasts, 2013)

Different plant traits affect two pathways of riparian nitrogen removal in a restored freshwater wetland - A. E. Sutton-Grier; J. P. Wright; C. J. Richardson (Plant and Soil, 2013)

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

The Perceived Impact of Customary Marine Resource Management on Household and Community Welfare in Northern Sumatra, Indonesia - Adityo Setiawan; Joshua E. Cinner; Stephen G. Sutton; Ahmad Mukminin (Coastal Management, 2012)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Comparison of microbial communities in pilot-scale bioreactors treating Bayer liquor organic wastes - Naomi J. McSweeney; Jason J. Plumb; Amanda L. Tilbury; Hugh J. Nyeboer; Matt E. Sumich; Anthony J. McKinnon; Peter D. Franzmann; David C. Sutton; Anna H. Kaksonen (Biodegradation, 2011)

Isolation and development of 12 polymorphic tetranucleotide microsatellite markers for the eastern hellbender (Cryptobranchus alleganiensis alleganiensis) - Shem D. Unger; Jennifer A. Fike; Trent Sutton; Olin E. Rhodes; Rod N. Williams (Conservation Genetics Resources, 2010)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

The evolution of two homologues of the core protein VP6 of epizootic haemorrhagic disease virus (EHDV), which correspond to the geographical origin of the virus - S. J. Anthony; K. E. Darpel; S. Maan; G. Sutton; H. Attoui; P. P. C. Mertens (Virus Genes, 2010)

The inheritance of chemical phenotype in Cannabis sativa L. (IV): cannabinoid-free plants - E. P. M. de Meijer; K. M. Hammond; A. Sutton (Euphytica, 2009)

Organic amendments improve soil conditions and denitrification in a restored riparian wetland - Ariana E. Sutton-Grier; Mengchi Ho; Curtis J. Richardson (Wetlands, 2009)

Consequences of injuries on survival and reproduction of common bottlenose dolphins ( Tursiops truncatus ) along the west coast of Florida - Randall S. Wells; Jason B. Allen; Suzanne Hofmann; Kim Bassos‐Hull; Deborah A. Fauquier; Nélio B. Barros; Ruth E. DeLynn; Gretchen Sutton; Victoria Socha; Michael D. Scott (Marine Mammal Science, 2008)
Accurate identification of human‐induced injuries that lead to death or interfere with reproduction is important for marine mammal management, as deaths exceeding established limits can lead to restrictions on fisheries or vessel operations. The fates of cetaceans last seen swimming with attached gear, particularly in pelagic fisheries, or with vessel strike lacerations, have been difficult to predict. Survival and reproduction data from long‐term research on resident common bottlenose dolphins near Sarasota, Florida were examined relative to consequences of fishing gear ingestion, line entanglements, vessel strikes, and amputations of unknown origins. Fishing hooks embedded in the throat, goosebeak, or esophagus, or line wrapped around the goosebeak, generally lead to death. Multiple, constrictive line wraps around fin insertions can lead to amputation, blood loss, impaired mobility, or infection. Dolphins with ingested gear or severe entanglements may swim away with the gear, but likely die later. Propeller injuries involving only soft tissue were often survivable. Some dolphins survived amputations of the distal ends of fins, and continued to reproduce. As a precautionary approach, dolphins with ingested gear or severe constrictive entanglements should be considered mortalities, but extrapolations of findings from coastal bottlenose dolphins to other cetaceans and different gear must be done with caution.

Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - MARK A. SUTTON; DAVID SIMPSON; PETER E. LEVY; ROGNVALD I. SMITH; STEFAN REIS; MARCEL Van OIJEN; WIM De VRIES (Global Change Biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEP av ) for midlatitude forests, with an extremely high C to N response (725 kg C kg −1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be et al. Multisite regression of simulated NEP av vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.

Socioeconomic Thresholds That Affect Use of Customary Fisheries Management Tools - JOSHUA E. CINNER; STEPHEN G. SUTTON; TREVOR G. BOND (Conservation Biology, 2007)
Customary forms of resource management, such as taboos, have received considerable attention as a potential basis for conservation initiatives in the Indo‐Pacific. Yet little is known about how socioeconomic factors influence the ability of communities to use customary management practices and whether socioeconomic transformations within communities will weaken conservation initiatives with a customary foundation. We used a comparative approach to examine how socioeconomic factors may influence whether communities use customary fisheries management in Papua New Guinea. We examined levels of material wealth (modernization), dependence on marine resources, population, and distance to market in 15 coastal communities. We compared these socioeconomic conditions in 5 communities that used a customary method of closing their fishing ground with 10 communities that did not use this type of management. There were apparent threshold levels of dependence on marine resources, modernization, distance to markets ( 600 people) beyond which communities did not use customary fisheries closures. Nevertheless, economic inequality, rather than mean modernization levels seemed to influence the use of closures. Our results suggest that customary management institutions are not resilient to factors such as population growth and economic modernization. If customary management is to be used as a basis for modern conservation initiatives, cross‐scale institutional arrangements such as networks and bridging organizations may be required to help filter the impacts of socioeconomic transformations.

On the climate response of the low-latitude Pacific Ocean to changes in the global freshwater cycle - P. D. Williams; E. Guilyardi; R. T. Sutton; J. M. Gregory; G. Madec (Climate Dynamics, 2006)

Chemical Signal Mediated Premating Reproductive Isolation in a Marine Polychaete, Neanthes acuminata (Arenaceodentata) - R. Sutton; E. Bolton; H. D. Bartels-Hardege; M. Eswards; D. J. Reish; J. D. Hardege (Journal of Chemical Ecology, 2005)

Economics of Intensively Managed Forest Plantations in the Pacific Northwest - Glen E. Murphy; Wink R. J. Sutton; Denny Hill; Charles Chambers; Dennis Creel; Clark Binkley; David New (Journal of Forestry, 2005)
Lower risks and higher returns favor investment in intensively managed forest plantations in the Pacific Northwest (PNW) for industrial landowners. Intensive forest plantation management is necessary if PNW industrial landowners are to compete effectively in world markets. However, not all landowner classes have the same set of management objectives, investment streams, and performance measures. For a variety of reasons, intensive forest plantation management may not be appropriate for some nonindustrial and public lands.

Neural control exploits changing mechanical advantage and context dependence to generate different feeding responses in Aplysia - Gregory P. Sutton; Elizabeth V. Mangan; David M. Neustadter; Randall D. Beer; Patrick E. Crago; Hillel J. Chiel (Biological Cybernetics, 2004)

Passive hinge forces in the feeding apparatus of Aplysia aid retraction during biting but not during swallowing - G. P. Sutton; J. B. Macknin; S. S. Gartman; G. P. Sunny; R. D. Beer; P. E. Crago; D. M. Neustadter; H. J. Chiel (Journal of Comparative Physiology A, 2004)

An intercomparison between the surface heat flux feedback in five coupled models, COADS and the NCEP reanalysis - C. Frankignoul; M. Botzet; A. F. Carril; E. Kestenare; H. Drange; A. Pardaens; L. Terray; R. Sutton (Climate Dynamics, 2004)

Y Chromosome and Other Heterochromatic Sequences of the Drosophila Melanogaster Genome: How Far can we go? - A. Bernardo Carvalho; Maria D. Vibranovski; Joseph W. Carlson; Susan E. Celniker; Roger A. Hoskins; Gerald M. Rubin; Granger G. Sutton; Mark D. Adams; Eugene W. Myers; Andrew G. Clark (Genetica, 2003)

A climatology of leaf surface wetness - O. Klemm; C. Milford; M. A. Sutton; G. Spindler; E. van Putten (Theoretical and Applied Climatology, 2002)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The Role of Guesswork in Conserving the Threatened Sand Skink - Earl D. McCoy; Phillip E. Sutton; Henry R. Mushinsky (Conservation Biology, 1999)
Because we possess little understanding of what constitutes optimal habitat for the threatened sand skink, any individual charged with choosing among habitat fragments to promote recovery of the species will need to employ some guesswork. We examined the relative values of employing two kinds of guesswork, “uneducated guesswork,” from literature descriptions of optimal habitat, and “educated guesswork,” from expert judgments of optimal habitat. The rank order of seven areas of scrub habitat in central Florida based on abundance of the sand skink ( Neoseps reynoldsi ) was compared with the rank order of the areas based on literature descriptions and on expert judgments. Ranks of areas based on expert judgments predicted ranks of areas based on sand skink abundance much better than did ranks of areas based on literature descriptions. Our results show, on the one hand, how uneducated guesswork could challenge recovery of the sand skink and, on the other hand, how educated guesswork could support its recovery.

Transfer cell induction in cotyledons ofVicia faba L. - C. E. Offler; E. Liet; E. G. Sutton (Protoplasma, 1997)